Primary Anterior Teeth Rehabilitation with 3D‑Printed Resin Crowns in a Digital Workflow: Case Report - Porras Zúñiga, Alejandra (2026)
Severe early childhood caries is among the most prevalent oral conditions in children and may significantly affect health, esthetics, and self-esteem. Finding restorative solutions that are both functional, esthetic, and well accepted by young patients can be a clinical challenge, especially in primary anterior teeth with extensive structural loss. This report presents the case of a 5-year-2-month-old boy with multiple carious lesions in the primary dentition, a high caries risk profile, and a strong esthetic concern shared by both the child and his mother. After completing the urgent and stabilization phases, the maxillary primary incisors were rehabilitated using 3D-printed crowns, prioritizing patient comfort and procedural simplicity. The digital workflow included intraoral scanning, customized anatomical design with Exocad® DentalDB 3.2, and additive manufacturing using biocompatible Crowntec® resin. The crowns were placed without complications and with excellent patient cooperation. Follow-up visits at one, three, and six months demonstrated proper adaptation, stability, and excellent gingival response. Both the child and his mother expressed satisfaction with the esthetic and functional outcome. The use of 3D-printed crowns in pediatric patients with early childhood caries represents a viable and effective restorative option that combines technical precision with esthetic, emotional, and psychosocial benefits, contributing not only to oral health but also to the child’s overall well-being.